White ink composition suitable for ink-jet 3D printing and preparation method thereof

By using a specific ratio of white ink compositions, including oligomers and nanotitanium dioxide slurries in inkjet 3D printing, the problems of ink settlement, yellowing and low mechanical properties are solved, achieving a more stable printing effect and Higher ink flow.

CN119161541APending Publication Date: 2024-12-20JINHUA CREATION NEW MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311727913.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing white inks printed by inkjet 3D have problems such as fast settling speed, yellowing of the material after curing, low mechanical properties after curing, and poor jet fluency, which affects the printing effect and product stability.

Method used

Using 100 parts of a white ink composition of mass, including 20-50 parts of oligomer, 45-75 parts of the first active diluent, 0.5-3 parts of the photoinitiator and 1-4 parts of the nano-titanium dioxide slurry, through the oligomer The choice of nanotitanium dioxide grinding and surface coating technology optimizes the viscosity, curing rate and mechanical properties of the ink, combined with specific additives to improve the stability and ejection properties of the ink.

Benefits of technology

It significantly reduces the settlement rate of nano-titanium dioxide, improves color accuracy and the stability of printing products, ensures high viscosity and smoothness of ink during storage and printing, and meets the requirements for color accuracy and printing products. , and remove impurities by filtration to extend the life of the print head.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004609204340000091
    Figure BDA0004609204340000091
  • Figure BDA0004609204340000101
    Figure BDA0004609204340000101
  • Figure BDA0004609204340000102
    Figure BDA0004609204340000102
Patent Text Reader

Abstract

The invention discloses a white ink composition suitable for ink-jet 3D printing and a preparation method thereof, and the white ink composition comprises the following substances in parts by mass based on 100 parts by mass of the white ink composition: 20-50 parts of oligomer; 45 to 75 parts of a first active diluent, wherein the first active diluent is one or two of monofunctional acrylic ester and bifunctional acrylic ester; 0.5-3 parts of a photoinitiator and 1-4 parts of nano titanium dioxide slurry, and the average particle size of titanium dioxide in the nano titanium dioxide slurry is 60-80 nm. The white ink composition disclosed by the invention is low in settling velocity, the color of the cured material is not easy to yellow, the mechanical property of the cured material is good, and the jet fluency is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of inkjet 3D printing, and in particular to a white ink composition and a preparation method thereof. Background Art

[0002] Polymer jetting technology is to spray a thin layer of liquid polymer material that can be cured by ultraviolet light through multiple nozzles on a flat platform, and use hot melt or solution soluble materials as support during the printing process. It is cured layer by layer under ultraviolet light. After each layer is completed, the modeling table will drop and make another layer. The above process is repeated until the entire part is printed. Inkjet 3D printers that use polymer jetting technology can provide a Z-axis resolution layer thickness of up to 10 microns, and can print high-precision fine parts.

[0003] As an advanced manufacturing process, polymer jetting technology has been widely used in various fields, such as portrait printing, cosmetic packaging, rapid tooling, jigs and fixtures, conceptual models, quick assembly testing, functional prototypes, and medical applications. However, in many applications, the performance and quality of the printing material have an important influence on the printing effect, and high requirements are placed on the color accuracy and stability of the printed product. Currently, the white inks available on the market generally have some problems, such as fast sedimentation speed, yellowing of the material after curing, low mechanical properties of the material after curing, and jetting smoothness. Therefore, it is of great significance to develop a high-quality white ink material suitable for inkjet 3D printing and a preparation method thereof. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a stable white ink composition suitable for inkjet 3D printing and a preparation method thereof, so as to meet the requirements for color accuracy and stability of printed products.

[0005] The present invention adopts the following technical solutions:

[0006] A white ink composition suitable for inkjet 3D printing, comprising the following substances in parts by mass based on 100 parts by mass of the white ink composition:

[0007] Oligomer: 20-50 parts,

[0008] The first reactive diluent: 45-75, wherein the first reactive diluent is one or both of monofunctional acrylate and difunctional acrylate;

[0009] Photoinitiator: 0.5-3 parts,

[0010] Nano titanium dioxide slurry: 1-4 parts, wherein the average particle size of titanium dioxide in the nano titanium dioxide slurry is between 60-80 nm.

[0011] The main role of the oligomer in the above components is: in the UV curing system, the oligomer basically determines the performance of the cured material, so the selection of the oligomer is undoubtedly the most important link in the design of the formulation of the photocurable product. The selection of the oligomer of the present invention comprehensively considers the following factors: 1. Viscosity: The use of low-viscosity oligomers can reduce the amount of reactive diluents, but low-viscosity oligomers often have low molecular weights, which will affect the mechanical properties of the cured material. 2. Photocuring rate: For inkjet 3D printing technology, free radical systems and surface oxygen inhibition are important factors affecting the curing rate of materials. The selection of oligomers with fast photocuring rates is an important condition, which can not only reduce the amount of photoinitiators, but also reduce the problem of yellowing of the cured product caused by the addition of photoinitiators. Generally speaking, the higher the functionality, the faster the curing rate, and the reaction rate of epoxy acrylate and amine-modified oligomers is faster. 3. Mechanical properties: The mechanical properties of photocurable materials mainly include the following properties: hardness, flexibility, wear resistance, impact resistance, tensile strength, and flexural strength. 4. Yellowing resistance: Aliphatic and alicyclic polyurethane acrylate oligomers, polyether acrylate oligomers and pure acrylate oligomers have good yellowing resistance. 5. Chemical resistance: Epoxy acrylate, polyurethane acrylate and polyester acrylate have good chemical resistance, but polyester acrylate has poor alkali resistance. 6. Toxicity and irritation: Oligomers with low toxicity and irritation should be selected.

[0012] Preferably, the absolute value of the slope of the oligomer corresponding to two points on the abscissa 25°C and 60°C of the viscosity-temperature curve is greater than 40. Figure 1 It can be seen from the viscosity-temperature curve of the oligomer that the viscosity change rate of different oligomers from 25-70°C is significantly different. The oligomer (such as CN1964NS) with the absolute value of the slope of the two corresponding points on the horizontal axis 25°C and 60°C curve> 40 is preferred. The corresponding oligomers on the curve: BDT-1006, BR940BT, BR970BT are produced by Dymax; QR8698, QR8697, SD7801B are produced by Zhejiang Jiaxing Sudi Polymer Materials Co., Ltd.; CN991NS, CN1964NS are produced by Arkema. Its main purpose is to have a higher viscosity when the ink is stored at room temperature, and have a suitable viscosity when printing (50-70°C), so as to avoid the rapid sedimentation of titanium dioxide during storage, resulting in inaccurate color and poor stability of printed products. At the same time, this type of oligomer has good yellowing resistance.

[0013] Furthermore, the oligomer is one or both of aliphatic polyurethane acrylate and polyether polyurethane acrylate.

[0014] The main functions of the first active diluent are to dissolve and dilute the oligomer, adjust the viscosity of the system, participate in the photocuring process, and affect the curing speed of the photocurable material and the various properties of the cured material.

[0015] Preferably, every 100 parts by mass of the nano titanium dioxide slurry comprises: 25-60 parts of white slurry raw material, 25-60 parts of a second active diluent, 1-10 parts of a second wetting and dispersing agent, and 5-15 parts of a silane coupling agent. The mass content of titanium dioxide in the nano titanium dioxide slurry is 12.5% ​​to 30%.

[0016] Preferably, the second reactive diluent is one or more of 2-phenoxyethyl acrylate, cyclotrimethylolpropane formal acrylate, 4-acryloylmorpholine, and isobornyl acrylate; the second wetting and dispersing agent is one or more of a polysiloxane dispersant (such as BYK-377, BYK378), a copolymer containing a pigment affinity group (such as DISPERBYK-2013, DISPERBYK-2013) (the second wetting and dispersing agents are all produced by BYK Chemical); the silane coupling agent is one or both of γ-methacryloxypropyltrimethoxysilane and γ-methacryloxypropyltriethoxysilane.

[0017] Preferably, the nano-titanium dioxide slurry is prepared by the following method: weigh corresponding weights of white slurry raw material, a second active diluent, a second wetting dispersant and a silane coupling agent, add them into a bead mill and grind them with 0.1 mm grinding beads, and control the grinding temperature between 25-40°C, take them out after 5-10 hours of cyclic grinding, and then filter and defoam for standby use.

[0018] The main function of the first / second wetting and dispersing agent is that after titanium dioxide is ground or dispersed into fine particles, it is evenly distributed in the continuous phase of the ink base to obtain a relatively stable suspension. The dispersion of titanium dioxide must go through three processes: wetting, crushing and stabilization. Wetting is the process of replacing the air or water adsorbed on the surface of titanium dioxide with resin or additives to change the solid / gas interface into a solid / liquid interface; crushing is to break up the initial particles or agglomerated particles of titanium dioxide with mechanical force to obtain titanium dioxide with smaller particle size and particle size distribution to form a suspended dispersion; stability means that the formed suspension can still be in a dispersed and suspended state without external force. The wetting and dispersing agent mainly reduces the surface tension of the system, adsorbs on the surface of titanium dioxide to produce charge repulsion or steric hindrance, and prevents titanium dioxide from agglomerating. To obtain a good and stable dispersed white ink, it is often necessary to use a wetting and dispersing agent to achieve the best effect.

[0019] The photoinitiator is a key component of the photocurable material, and it plays a decisive role in the curing speed of the photocurable product. Preferably, the photoinitiator is a cleavage-type free radical photoinitiator, such as one or more of 1173, 184, TPO, TPO-L, and 819.

[0020] Preferably, the white ink composition also includes 0.05-1 part of a first wetting and dispersing agent, 0.05-1 part of a leveling agent, and 0.05-1 part of a defoaming agent, wherein the first wetting and dispersing agent is one or more of lecithin-based natural polymers, acids or polyamine salts of long-chain polyesters, polyvalent carboxylic acids, and polysiloxanes; the leveling agent is one or more of fluorinated polyacrylates, acrylate copolymers, and siloxanes; the defoaming agent is one or both of non-silicone defoamers and silicone defoamers.

[0021] Preferably, the white ink composition further comprises 0.05-1 part of an in-can storage stabilizer, wherein the in-can storage stabilizer is one or both of an aerobic polymerization inhibitor and an anaerobic polymerization inhibitor.

[0022] The main functions of defoamers, leveling agents, and in-can storage stabilizers are to meet some functional uses of the product, improve and optimize some defects of the material itself, so as to meet the requirements for color accuracy and stability of printed products.

[0023] The present invention also provides a method for preparing the white ink composition, comprising the following steps:

[0024] (1) Preparation of nano titanium dioxide slurry: weigh the corresponding weight of white slurry raw material, the second active diluent, the second wetting dispersant and the silane coupling agent, add them into a bead mill and grind them with 0.1 mm grinding beads, and control the grinding temperature between 25-40° C. After 5-10 hours of cyclic grinding, take them out, and then filter them with 1 μm and 0.45 μm filters and defoam them for later use;

[0025] (2) Weigh corresponding weights of oligomer, first reactive diluent, photoinitiator, nano titanium dioxide slurry, first wetting and dispersing agent, leveling agent, defoaming agent, and tank storage stabilizer, and stir them thoroughly at 50-70° C. and 1000-2000 rad / min for 2-5 hours using a high-speed stirrer;

[0026] (3) The white ink composition stirred in step (2) is filtered through filters of 1 micron and 0.45 micron, respectively, and then the filtered white ink composition is stored in an environment of 15-25° C. and away from light for later use.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] Most white inks used for inkjet printing on the market use nano titanium dioxide white pigments. However, nanoparticles are easy to agglomerate into aggregates due to their small particle size, large specific surface area, high surface energy, thermodynamically unstable state and special surface structure, resulting in unstable jetting during printing and color instability after agglomeration and sedimentation.

[0029] In order to overcome these problems of mainstream products on the market, the present invention combines nano white slurry grinding with surface coating technology, mixes the nano white slurry with one or more other substances, and finely grinds under certain conditions to obtain a nano white slurry with a finer particle size, a more uniform particle size distribution, and a more stable particle size distribution. Then, through the titanium dioxide surface coating technology, other substances form one or more layers of thin films on the surface of the nano white slurry, thereby improving its surface properties and further increasing its dispersion stability.

[0030] Secondly, the oligomer of the present invention uses an oligomer or active diluent that is sensitive to temperature changes, and has the characteristics of high viscosity at low temperature and low viscosity at high temperature, thereby ensuring that the ink has a higher viscosity under room temperature storage environment, greatly reducing the sedimentation rate of nano titanium dioxide, and the ink viscosity at high temperature (50-70°C) can have a lower jetting viscosity, meeting the requirements for color accuracy and stability of printed products. By controlling the dosage ratio of special oligomers and active diluents, cured materials with different rigidity and toughness can be obtained.

[0031] In addition, using a filter with a certain pore size to filter the ink can effectively remove particles and impurities, thereby improving the life of the print head and printing quality; adding additives in specific proportions and types changes the surface tension and rheological properties of the ink material, thereby obtaining better printing quality on the model surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Viscosity-temperature curves of several oligomers;

[0033] Figure 2 is the particle size distribution diagram of nano titanium dioxide slurry;

[0034] Figure 3 Particle size distribution of the original unground W-PUV9008 slurry. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the technical solution of the present invention, a detailed description is given below in conjunction with the accompanying drawings and specific embodiments.

[0036] Example 1

[0037] (1) Preparation of nano titanium dioxide slurry:

[0038] Weigh 50 parts of W-PUV9008 stock (produced by Shanghai Wangchong Chemical, with a titanium dioxide content of 50%), 30 parts of active diluent: 2-phenoxyethyl acrylate (produced by Mitsubishi, Japan), 10 parts of wetting and dispersing agent: BYK-377 (produced by BYK), and 10 parts of silane coupling agent: γ-methacryloxypropyl trimethoxysilane (produced by Momentive). Then put the above substances into Cenomic TM A full volume bead mill (produced by Buhler) was used with 0.1 mm equipment equipped with special grinding beads, and the grinding temperature was controlled between 25-40°C. After 6 hours of cyclic grinding, the mill was taken out and then filtered with 1 micron and 0.45 micron filters. After filtering, the nano titanium dioxide slurry and W-PUV9008 original slurry were tested for particle size distribution. The results were as follows: Figure 2 , Figure 3 As shown, comparing before and after grinding, the titanium dioxide particle size distribution before grinding is between 100-1000nm, and the average particle size is 307.2nm. After grinding, 95% of the titanium dioxide particle size is distributed between 10nm-100nm, and the average particle size is 73.5nm. The titanium dioxide particle size and particle size distribution are significantly reduced.

[0039] (2) Weigh the following materials: 25 parts of oligomer BR-970BT (produced by Dymax), 15 parts of active diluent: 4-acryloylmorpholine (produced by Mitsubishi Chemical), 15 parts of isobornyl acrylate (produced by Evonik Specialty Chemicals), 15 parts of trimethylolcyclohexyl acrylate (produced by Evonik Specialty Chemicals), 14 parts of cyclotrimethylolpropane formal acrylate (produced by Mitsubishi Chemical), 10 parts of tricyclodecane dimethanol diacrylate (produced by Arkema); 2 parts of photoinitiator TPO (produced by IGM), 4 parts of nano titanium dioxide slurry. Stir thoroughly for 3 hours at 60°C and 1500 rad / min in a high-speed stirrer;

[0040] (3) The white ink composition stirred in step (2) is filtered through filters of 1 micron and 0.45 micron, respectively, and then the filtered white ink composition is stored in an environment of 15-25° C. and away from light for later use.

[0041] Example 2

[0042] Except that the material ratio in step (2) is as follows: 25 parts of oligomer BR-952 (produced by Dymax), 15 parts of reactive diluent: 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 14 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate, 2 parts of photoinitiator TPO, 4 parts of nano titanium dioxide slurry, the remaining steps are the same as those in Example 1. The same material is produced by the same manufacturer, and will not be described in detail in other places in the text when it first appears.

[0043] Example 3

[0044] Except for the following material ratios in step (2): 50 parts of oligomer BR-952, 15 parts of reactive diluent: 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 14 parts of cyclotrimethylolpropane formal acrylate, 2 parts of photoinitiator TPO, and 4 parts of nano titanium dioxide slurry, the remaining steps are the same as those in Example 1.

[0045] Example 4

[0046] Except for the following material ratios in step (2): oligomer: 10 parts of BR-970BT, 20 parts of BR-952, active diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 9 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate; 2 parts of photoinitiator TPO, 4 parts of nano titanium dioxide slurry. The remaining steps are the same as in Example 1.

[0047] Example 5

[0048] Except for the following material ratios in step (2): oligomer: 20 parts of BR-970BT, 10 parts of BR-952; reactive diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 9 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate, 2 parts of photoinitiator TPO; 4 parts of nano titanium dioxide slurry. The remaining steps are the same as in Example 1.

[0049] Example 6

[0050] Except for the following material ratios in step (2): oligomer: 20 parts of BR-970BT, 10 parts of BR-952; reactive diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 8.5 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate; 2 parts of photoinitiator TPO, 4 parts of nano titanium dioxide slurry, 0.5 parts of wetting dispersant BYK-110 (produced by BYK). The remaining steps are the same as those in Example 1.

[0051] Example 7

[0052] Except for the following material ratios in step (2): 20 parts of oligomer BR-970BT, 10 parts of BR-952; active diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 8.3 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate, 2 parts of photoinitiator TPO; 4 parts of nano titanium dioxide slurry, 0.5 parts of wetting dispersant BYK-110; 0.2 parts of defoamer BYK-088 (produced by BYK). The remaining steps are the same as in Example 1.

[0053] Example 8

[0054] Except for the following material ratios in step (2): oligomer: 20 parts of BR-970BT, 10 parts of BR-952; reactive diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 8.25 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate; 2 parts of photoinitiator TPO; 4 parts of nano titanium dioxide slurry, 0.5 parts of wetting dispersant BYK-110, 0.2 parts of defoamer BYK-088, 0.05 parts of leveling agent BYK-377 (produced by BYK). The remaining steps are the same as those in Example 1.

[0055] Example 9

[0056] Except for the following material ratios in step (2): oligomer: 20 parts of BR-970BT, 10 parts of BR-952; reactive diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 7.75 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate; 2 parts of photoinitiator TPO; 4 parts of nano titanium dioxide slurry; 0.5 parts of wetting and dispersing agent BYK-110; 0.2 parts of defoaming agent BYK-088, 0.05 parts of leveling agent BYK-377, and 0.5 parts of in-can storage stabilizer GENORAD*20 (produced by RAHA). The remaining steps are the same as in Example 1.

[0057] Example 10

[0058] Except for the following material ratios in step (2): oligomer: BR-970BT: 10 parts, BR-952: 20 parts; active diluent: 4-acryloylmorpholine: 15 parts, isobornyl acrylate 15 parts, trimethylolcyclohexyl acrylate 15 parts, cyclotrimethylolpropane formal acrylate 7.75 parts, tricyclodecane dimethanol diacrylate 10 parts, photoinitiator TPO 2 parts, nano titanium dioxide slurry 4 parts, wetting dispersant BYK-110 0.5 parts, defoamer BYK-088 0.2 parts; leveling agent BYK-377 0.05 parts, tank storage stabilizer GENORAD*20 0.5 parts. The remaining steps are the same as in Example 1.

[0059] Comparative Example 1

[0060] The material ratios in step (2) are as follows: 20 parts of oligomer BR-970BT and 10 parts of BR-952; active diluent: 15 parts of 4-acryloylmorpholine, 15 parts of isobornyl acrylate, 15 parts of trimethylolcyclohexyl acrylate, 7.75 parts of cyclotrimethylolpropane formal acrylate, 10 parts of tricyclodecane dimethanol diacrylate, 2 parts of photoinitiator TPO, 4 parts of unground nano titanium dioxide slurry (compared with step (1) of Example 1, except that ball mill grinding is not used, the proportions of other components are the same), 0.5 parts of wetting and dispersing agent BYK-110, 0.2 parts of defoaming agent BYK-088, 0.05 parts of leveling agent BYK-377, and 0.5 parts of in-can storage stabilizer GENORAD*20.

[0061] The products of Examples 1-10 and Comparative Example 1 were filtered, left to stand for 24 hours to defoam, and then subjected to viscosity test, room temperature sedimentation test, 60°C high temperature storage stability test, and printing test. Finally, the evaluation results of the liquid white ink and the cured material shown in Tables 1 and 2 were obtained:

[0062] Table 1 Liquid white ink evaluation

[0063]

[0064]

[0065] Evaluation table 2 of cured materials

[0066]

[0067] Comparative Examples 1-10 and Comparative Example 1, the ink viscosity is between 7-12 mps, meeting the basic printing jetting requirements.

[0068] Comparing Example 1 and Example 2, although the two solutions start to settle at the same time, the viscosity of Example 1 at 60°C is 11 mps> that of Example 2, which is 7 mps. Therefore, oligomer BR-952 is more suitable as the matrix resin of the titanium dioxide anti-settling system. The fundamental reason is that the viscosity change rate of BR-952 from low temperature to high temperature is greater than that of BR-970BT.

[0069] Comparing Examples 1-10 with Comparative Example 1, the initial sedimentation time of Comparative Example 1 is 7 days, which is significantly shorter than that of other solutions. The fundamental reason is that the titanium dioxide particle size and particle size distribution of Comparative Example 1 are larger, and no surface treatment has been done.

[0070] Comparing Examples 1-8 with Examples 9-10 and Comparative Example 1, the viscosity change rate of Examples 1-8 after storage at 60°C for 30 days was 2%, while the viscosity change rate of Examples 9-10 and Comparative Example 1 after storage at 60°C for 30 days was 0%. The fundamental reason lies in whether the in-tank storage stabilizer is added.

[0071] Comparing Examples 1-10 and Comparative Example 1, the nano titanium dioxide color paste of the present invention has good spraying smoothness and color stability. Comparative Example 1 uses the nano color paste without any treatment, which blocks the nozzle and the color becomes lighter after storage. The fundamental reason is that the particle size, particle size distribution, specific surface area and particle shape of titanium dioxide have changed significantly.

[0072] Comparative Examples 1-6, Example 7, Examples 8-10, and Comparative Example 1, Examples 1-6 did not add defoamers, and the surface was rough and accompanied by a small amount of foaming. Defoamers were added to Example 7, and the pores disappeared. Examples 8-10 and Comparative Example 1, the addition of defoamers and leveling agents gave the model a better surface quality. The fundamental reason is that the addition of defoamers and leveling agents changes the surface tension and rheological properties of the ink, thereby ensuring good surface printing quality.

[0073] Compared with Examples 1-10 and Comparative Example 1, different proportions of oligomers show different mechanical properties. When two oligomers are used in combination, the cured material can have both high toughness and bending strength. The proportion of oligomers or reactive diluents can be adjusted according to the use requirements to adjust the mechanical properties of the cured material.

[0074] The above are only preferred embodiments of the present invention. The protection scope of the present invention shall be based on the scope defined by the claims. Several improvements and modifications made by those skilled in the art without departing from the spirit and scope of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A white ink composition suitable for inkjet 3D printing, characterized in that, based on 100 parts by mass of the white ink composition Contains the following substances in parts by weight: Oligomer: 20-50 parts; The first reactive diluent: 45-75, wherein the first reactive diluent is one or both of monofunctional acrylate and difunctional acrylate; Photoinitiator: 0.5-3 parts; Nano titanium dioxide slurry: 1-4 parts, wherein the average particle size of titanium dioxide in the nano titanium dioxide slurry is between 60-80 nm.

2. The white ink composition according to claim 1, wherein: The absolute values ​​of the slopes of the oligomer corresponding to two points on the abscissa 25° C. and 60° C. of the viscosity-temperature curve are greater than 40.

3. The nano titanium dioxide slurry added to the white ink composition according to claim 1, characterized in that: Every 100 parts by mass of the nano titanium dioxide slurry contains: 25-60 parts of white slurry raw material, 25-60 parts of a second active diluent, 1-10 parts of a second wetting dispersant, and 5-15 parts of a silane coupling agent. The mass content of titanium dioxide in the nano titanium dioxide slurry is 12.5%-30%.

4. The white ink composition according to claim 3, characterized in that: The second active diluent is one or more of 2-phenoxyethyl acrylate, cyclotrimethylolpropane formal acrylate, 4-acryloylmorpholine, and isobornyl acrylate; the second wetting and dispersing agent is one or more of a polysiloxane dispersant and a copolymer containing a pigment affinity group; the silane coupling agent is one or two of γ-methacryloxypropyltrimethoxysilane and γ-methacryloxypropyltriethoxysilane.

5. The white ink composition according to claim 4, characterized in that: The nano titanium dioxide slurry is prepared by the following method: weighing corresponding weights of white slurry raw material, second active diluent, second wetting dispersant and silane coupling agent, adding them into a bead mill and grinding them with 0.1 mm grinding beads, and controlling the grinding temperature between 25-40° C., taking them out after cyclic grinding for 5-10 hours, filtering and defoaming for standby use.

6. The white ink composition according to claim 1 or 2, characterized in that: The oligomer is one or both of aliphatic polyurethane acrylate and polyether polyurethane acrylate; the photoinitiator is a cleavage-type free radical photoinitiator.

7. The white ink composition according to claim 1, wherein: The white ink composition also includes 0.05-1 part of a first wetting and dispersing agent, 0.05-1 part of a leveling agent, and 0.05-1 part of a defoaming agent. The first wetting and dispersing agent is one or more of lecithin-based natural polymers, acids or polyamine salts of long-chain polyesters, polyvalent carboxylic acids, and polysiloxanes; the leveling agent is one or more of fluorinated polyacrylates, acrylate copolymers, and siloxanes; the defoaming agent is one or both of non-silicone defoaming agents and siloxane defoaming agents.

8. The white ink composition according to claim 7, wherein: The white ink composition further comprises 0.05-1 part of an in-can storage stabilizer, wherein the in-can storage stabilizer is one or both of an aerobic polymerization inhibitor and an anaerobic polymerization inhibitor.

9. A method for preparing a white ink composition according to any one of claims 1 to 8, characterized in that The following steps are involved: (1) Preparation of nano titanium dioxide slurry: weigh the corresponding weight of white slurry raw material, the second active diluent, the second wetting dispersant and the silane coupling agent, add them into a bead mill and grind them with 0.1 mm grinding beads, and control the grinding temperature between 25-40° C. After 5-10 hours of cyclic grinding, take them out, and then filter them with 1 μm and 0.45 μm filters and defoam them for later use; (2) Weigh corresponding weights of oligomer, first reactive diluent, photoinitiator, nano titanium dioxide slurry, first wetting and dispersing agent, leveling agent, defoaming agent, and tank storage stabilizer, and stir them thoroughly at 50-70° C. and 1000-2000 rad / min for 2-5 hours using a high-speed stirrer; (3) The white ink composition stirred in step (2) is filtered through filters of 1 micron and 0.45 micron, respectively, and then the filtered white ink composition is stored in an environment of 15-25° C. and away from light for later use.